-y-12/5=3

Simple and best practice solution for -y-12/5=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -y-12/5=3 equation:



-y-12/5=3
We move all terms to the left:
-y-12/5-(3)=0
determiningTheFunctionDomain -y-3-12/5=0
We add all the numbers together, and all the variables
-1y-3-12/5=0
We multiply all the terms by the denominator
-1y*5-12-3*5=0
We add all the numbers together, and all the variables
-1y*5-27=0
Wy multiply elements
-5y-27=0
We move all terms containing y to the left, all other terms to the right
-5y=27
y=27/-5
y=-5+2/5

See similar equations:

| 6-6x=7x-9x—4 | | 3a+(5a-8)+(3a+14)=180 | | x+7.3=12.5 | | b+2/3=4 | | (4x7)=(2x-1) | | 3+7z=-z+6z-15 | | 18+12x=-54 | | -118=9x+1 | | x+4=6+3x–10x | | 3(-10x+50)=69 | | x/11-2=-8 | | –y–125=3 | | (x+7)/4=-12 | | t(-13)=28 | | -2.5x+3.8=-2x–4.3 | | 74=-7a+4 | | 6(n-77)=96 | | 5-n=18 | | 10-s=-8+8s | | 3x²=588 | | –m−3+1=–7−2m | | 7/2x+1/2x=1,1/2+5/2x | | d-433=-266 | | 3x+(7(0)=84 | | 5(2x-3=135 | | (p+28)+2p=106 | | 74=–7a+4 | | x+7/4=-12 | | (3x+11)=(18x-43) | | -4g+6=-6+2g | | 14/56=y/100 | | 3(a+4)+4=7 |

Equations solver categories